2016
DOI: 10.1097/aog.0000000000001418
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis After Hyperemesis Gravidarum

Abstract: Pregnancies complicated by hyperemesis gravidarum represent potentially high-risk clinical scenarios for electrolyte abnormalities and subsequent complications, including rhabdomyolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Potassium abnormalities have been noted to increase the mortality associated with hyperemesis. Case reports have identified profound hypokalemia leading to rhabdomyolysis in the setting of hyperemesis gravidarum [24]. …”
Section: Maternal Complicationsmentioning
confidence: 99%
“…Potassium abnormalities have been noted to increase the mortality associated with hyperemesis. Case reports have identified profound hypokalemia leading to rhabdomyolysis in the setting of hyperemesis gravidarum [24]. …”
Section: Maternal Complicationsmentioning
confidence: 99%
“…Indeed, hypokalemia is associated with emergency operative delivery (adjusted odds ratio: 2.7) [10]. It would be rare, but HG is also related to osmotic demyelinating syndrome due to hyponatremia [13], Wernicke's encephalopathy due to vitamin B1 (thiamine) deficiency [14] and hypokalemic myopathy [7,8]. Although intravenous treatment strategy is not established, it is reported that intravenous rehydration with 5% dextrose-0.9% saline or 0.9% saline solution in women hospitalized for HG produced similar outcomes [15].…”
Section: Hyperemesis Gravidarum (Hg)mentioning
confidence: 99%
“…Although the pathophysiological causal relationship is understandable, only two cases with simultaneous onset of rhabdomyolysis and diabetes insipidus (DI) due to HG associated hypokalemia have been reported [7,8]. We herein describe a rare and instructive case of HG followed by RFS associated hypokalemia induced rhabdomyolysis and nephrogenic DI, successfully treated with oral supplementation of potassium chloride tablets.…”
mentioning
confidence: 97%
“…The most common cause of hypokalaemia in pregnancy is hyperemesis gravidarum . Gitelman syndrome is the second most commonly reported cause of hypokalaemia .…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…33,34 The most common cause of hypokalaemia in pregnancy is hyperemesis gravidarum. 50 Gitelman syndrome is the second most commonly reported cause of hypokalaemia. 51 Unusual causes of hypokalaemia in pregnancy include pica/geophagia, excessive ingestion of caffeine or carbonated beverages, hyperventilation, renal tubular acidosis, and following administration of betamethasone.…”
Section: Plasma Osmolality and Sodiummentioning
confidence: 99%